Establishment of drought screening protocols for rice under field conditions - Sakai, T.; Duque E., Myriam Cristina; Vallejo Cabrera, Franco Alirio; Pompilio Martínez, César; Ishitani, Manabu (2010)
Protocols were established for screening rice genotypes for tolerance to water-limited conditions under field conditions. These protocols were successfully used to select the best genotypes for further experiments. Rice genotypes responded differently when subjected to water-limited conditions. Experiments conducted under field conditions indicated that rice genotypes Curinga and CT6241 performed much better in terms of grain yield under water-limited conditions than varieties Azucena, Nerica, CICA8 and Palmar. Curinga, CT6241, CICA8 and Palmar were selected for further studies. The first two genotypes are tolerant and whereas the last two are susceptible to water stress.